Oilerio sandaugų analizinio pratęsimo klausimu - Stankus, Eugenijus (Lietuvos matematikos rinkinys, 2000)
The sequence of generalized primes {v(p + kpα)} with rational prime numbers p and v  > 1/2,  0≤ k  ≤ 1, 0 ≤ α < 1 is considered. The analicity of corresponding Euler product Z (s; v, k, α)= ∏p (1 — (v (p + kpα))-s)-1 in the domain {s : σ > α} \ (∪ρ∪n { s= (xβ+ iγ)/n : α < x ≤ 1} ∪ (α; 1]), where ρ = β + iγ are the zeros of Riemann zeta function, is proved.